The Impact of Product Quality and Brand Equity on Online Purchasing Decisions by Lazada Users in Mojokerto - Al Hakim, Yusuf Rahman; Sigita, Dwi Sembe (Bulletin of Science, Technology and Society, 2023)
This study aims to analyze the impact of product quality and brand equity on online purchasing decisions by Lazada users in Mojokerto. Along with the rapid growth of the e-commerce market, this phenomenon is increasingly significant, especially during the pandemic. Product quality and brand equity are key factors in making online purchasing decisions. This study involved 100 respondents with an age range of 25-35 years and various educational backgrounds. The regression analysis results show that product quality and brand equity significantly influence online purchasing decisions. These findings indicate that efforts to improve product quality and build brand equity can be important strategies in optimizing sales performance and strengthening Lazada's position in the Mojokerto market.